From matrimonial practices to genetic diversity in Southeast Asian populations: the signature of the matrilineal puzzle. (2nd September 2019) - Ly, Goki; Laurent, Romain; Lafosse, Sophie; Monidarin, Chou; Diffloth, Gérard; Bourdier, Frédéric; Evrard, Olivier; Toupance, Bruno; Pavard, Samuel; Chaix, Raphaëlle
Abstract : In matrilineal populations, the descent group affiliation is transmitted by women whereas the socio-political power frequently remains in the hands of men. This situation, named the 'matrilineal puzzle', is expected to promote local endogamy as a coping mechanism allowing men to maintain their decision-making power over their natal descent group. In this paper, we revisit this 'matrilineal puzzle' from a population genetics' point of view. Indeed, such tendency for local endogamy in matrilineal populations is expected to increase their genetic inbreeding and generate isolation-by-distance patterns between villages. To test this hypothesis, we collected ethno-demographic data for 3261 couples and high-density genetic data for 675 individuals from 11 Southeast Asian populations with a wide range of social organizations: matrilineal and matrilocal populations (M), patrilineal and patrilocal populations (P) or cognatic populations with predominant matrilocal residence (C). We observed that M and C populations have higher levels of village endogamy than P populations, and that such higher village endogamy leads to higher genetic inbreeding. M populations also exhibit isolation-by-distance patterns between villages. We interpret such genetic patterns as the signature of the 'matrilineal puzzle'. Notably, our results suggest that any form of matrilocal marriage (whatever the descent rule is) increases village endogamy. These findings suggest that male dominance, when combined with matrilocality, constrains inter-village migrations, and constitutes an underexplored cultural process shaping genetic patterns in human populations. This article is part of the theme issue 'The evolution of female-biased kinship in humans and other mammals'.